EXPRESS: Safety Defects and Fuel Efficiency in the Automotive Industry - Jeon, Donggyu; Ball, George P.; Souza, Gilvan C. (Production and Operations Management, 2026)
Automotive manufacturers have been under intense pressure to improve the fuel efficiency, or miles per gallon (MPG), of their internal combustion engine (ICE) vehicles. Research that explores hidden costs of continuing to push the limits of ICE MPG is sparse. We analyze the relationship between the MPG of 643 unique model-engines produced and sold by 18 manufacturers over an 18-year period and 19,785 vehicle safety defects reported to the National Highway Traffic Safety Administration (NHTSA). Each additional MPG improvement is associated with a 17.5 percent increase in safety defects. Results are confirmed when using fuel prices as an instrument for MPG. In post-hoc analyses, we find that a 2011 federal government fuel efficiency policy change explains an increase in the adoption of MPG-enhancing engine technologies, which subsequently led to an increase in safety defects. Moreover, we find that an increase in MPG is associated with an increase in safety recalls, and that safety defects mediate the relationship between MPG and safety recalls. To address selection bias concerns, we confirm our results using a separate quality reporting channel, demonstrating that increases in MPG are associated with a reduction in JD Power Quality & Reliability ratings. We also examine a key alternative explanation, that increasing MPG causes vehicles to be driven more miles, inherently leading to more defects. No evidence is found for this alternative; in fact we find the opposite to be true: an increase in MPG is associated with lower mileage at the time of the defect, indicating that increasing MPG leads to both more and faster defects. For manufacturers, our results identify an unexpected downside to striving to meet aggressive, federally mandated fuel efficiency standards: less safe vehicles. For NHTSA, our findings identify a possible contradiction in their two key objectives: sustainability and safety. Our study leads to policy recommendations, which we were fortunate to present to NHTSA’s Associate Administrator for Vehicle Safety Research and members of his staff.